(untitled) (Psychology Travelogs, 2025)
The article explores the psychological state of family members of servicemen who have gone missing in action as a result of warfare. The aim of this article is to highlight the psychological characteristics of experiencing ambiguous loss in families of missing military personnel, as well as to summarize effective approaches to providing psychological support to such families in wartime conditions. Special attention is paid to the phenomenon of ambiguous loss, which is characterized by prolonged emotional stress, helplessness, and a disrupted sense of life direction. The text describes typical psychological reactions in this situation, including anxiety, guilt and social withdrawal. The article outlines practical approaches to providing psychological support to relatives of missing persons: normalizing emotional responses, establishing daily routines, using body-based self-regulation techniques, maintaining social contact, and seeking professional help. The authors of the article emphasize the importance of developing an interdisciplinary approach to supporting such families, in particular the cooperation of psychologists, social workers, chaplains, and the active role of non-governmental organizations. Special attention should be given to the creation of long-term psychological support programs for families experiencing prolonged grief and uncertainty. The role of mental health professionals and volunteer initiatives is highlighted as essential in helping families preserve emotional resilience, strengthen coping strategies, adapt to the reality of uncertainty, and continue the search for their loved ones while taking care of their own well-being. This comprehensive approach ensures sustainable psychological assistance and promotes long-term resilience in the most vulnerable families.